PENGEMBANGAN LKPD IPA BERBASIS INKUIRI TERBIMBING PADA MATERI OPTIK UNTUK PESERTA DIDIK KELAS VIII - Nurul Fadhilatunnisa; Nur Kuswanti; Noer Af’idah (Discovery : Jurnal Ilmu Pengetahuan, 2021)
Developing science student worksheet based on Guided Inquiry optical object for grade eight was a general purpose of this study. The specific purposes were to describe the process of developing science student worksheet based on Guided Inquiry and its feasibility based on its validity. The development model used in this study was ADDIE that consiseds analysis, design, development, implementation, and evaluation. However, the implementation phase was not carried out due to a pandemic. The research questionnare method was a method used in the data collection process in this study. This development research resulted in a product in the form of a science student worksheet based on Guided Inquiry optical object for grade eight. The results of this development research indicate that the Science Student Worksheet Based on Guided Inquiry Optical Subject for Grade Eigth included in the very valid category because it obtained a validity scor of 3.79.